TRANSPORT OF Cr(III), Cd(II), Pb(II), AND Ag(I) IONS THROUGH BULK LIQUID MEMBRANE CONTAINING p-tert-BUTYLCALIX[4]ARENE –TETRAETHYLESTER AS ION CARRIER - Maming Maming; Jumina Jumina; Dwi Siswanta; Firdaus Firdaus; Hardjono Sastrohamidjojo (Indonesian Journal of Chemistry, 2008)
The study on transport of Cr(III), Cd(II), Pb(II), and Ag(I) through bulk liquid membrane using p-tert-butylcalix[4]arene-tetraethylester as ions carrier has been conducted. The aims of this work are to determine the optimum condition, efficiency, and selectivity of transport of the carriers for those ions. Both optimum condition and efficiency of transport were obtained by determination of the concentration of transported ions with variation of source phase pH, ion carrier concentration, the nature of stripping agent in the target phase, and transport time. The ion transport selectivity of ion carrier was obtained from the ions transport competition experiments using equimolar mixtures. The amount of Cr(III), Pb(II), Cd(II), and Ag(I  that was transported across liquid membrane was about 0, 10, 10 and 50 % respectively after 24 hours, except for Pb(II) (32 hours). The ion carrier is selective for Ag(I) where separation factor to Cd(II) was 16.0, that to Pb(II)was 42.8, and that to Cr(III) was infinite.